Evaluation of Alpha-1 Antitrypsin Levels and SERPINA1 Gene Polymorphisms in Sickle Cell Disease - Carvalho, Magda Oliveira Seixas; Souza, André Luís Carvalho Santos; Carvalho, Mauricio Batista; Pacheco, Ana Paula Almeida Souza; Rocha, Larissa Carneiro; Nascimento, Valma Maria Lopes do; Figueiredo, Camylla Vilas Boas; Guarda, Caroline Conceição; Santiago, Rayra Pereira; Adekile, Adekunle; Goncalves, Marilda de Souza (Frontiers in Immunology, 2017)
Alpha-1 antitrypsin (AAT) is an inhibitor of neutrophil elastase, and a member of the serine proteinase inhibitor (serpin) superfamily, and little is known about its activity in sickle cell disease (SCD). We hypothesize that AAT may undergo changes in SCD because of the high oxidative stress and inflammation associated with the disease. We have found high AAT levels in SCD patients compared to controls, while mutant genotypes of SERPINA1 gene had decreased AAT levels, in both groups. AAT showed negative correlation with red blood cells, hemoglobin, hematocrit, high-density lipoprotein cholesterol, urea, creatinine, and albumin; and was positively correlated with mean corpuscular hemoglobin concentration, white blood cells, neutrophils, hemoglobin S, bilirubin, lactate dehydrogenase, ferritin, and C-reactive protein. Patients with higher levels of AAT had more infection episodes (OR=1.71, CI: 1.05-2.65, p=0.02), gallstones (OR=1.75, CI: 1.03-2.97, p=0.02), and had more blood transfusions (OR=2.35, CI: 1.51-3.65, p=0.0001). Our data on AAT association with laboratory indices of hemolysis and inflammation suggest that it may be positively associated to SCD severity; the negative correlations with renal parameters suggest a cytoprotective mechanism in SCD patients. In summary, AAT may need to be included in studies related to SCD and in the discussion of further therapeutic strategies.